Pupillary Pain Index Changes After a Standardized Bolus of Alfentanil Under Sevoflurane Anesthesia: First Evaluation of a New Pupillometric Index to Assess the Level of Analgesia During General Anesthesia. (March 2019) - Sabourdin, Nada; Diarra, Coumba; Wolk, Risa; Piat, Véronique; Louvet, Nicolas; Constant, Isabelle
Abstract : BACKGROUND: The pupillary pain index (PPI) is a novel pupillometric index, designed to assess intraoperative analgesia. It is based on the evaluation of the pupillary response to electrical stimuli of increasing intensity. It ranges from 1 (low level of pupillary reactivity, high level of analgesia) to 10 (high level of pupillary reactivity, low level of analgesia). In this first evaluation of the PPI, our objective was to investigate the PPI changes after a bolus of 10 µg·kg −1 of alfentanil in children under sevoflurane general anesthesia. METHODS: After ethics committee approval and informed consent, 20 healthy children (9 ± 5 years) undergoing elective surgery under general anesthesia were included in this prospective, open, registered pilot study (NCT02646592). Anesthetic induction was standardized with sevoflurane 6% and propofol 1 mg·kg −1 . After tracheal intubation, sevoflurane concentration was maintained at 2% for 10 minutes. A first PPI measurement was performed (PPI-1), and a bolus of 10 µg·kg −1 was administered. Two minutes after this bolus, a second PPI measurement was performed (PPI-2). Heart rate, blood pressure, and bispectral index were recorded before and after each PPI measurement. Resting pupillary diameter was recorded before each PPI measurement. PPI scores before and after the bolus of alfentanil were compared using a Wilcoxon signed rank test. RESULTS: PPI scores decreased after administration of a bolus of alfentanil (median difference: −3 [95% confidence interval, −4 to −2]). The median (quartiles) of PPI-1 (baseline, before alfentanil) was 6 (4, 7), and the median (quartiles) of PPI-2 (after alfentanil) was 2 (2, 3) ( P < .001). No difference was found in resting pupillary diameter before PPI-1 and PPI-2 (2.2 ± 0.2 and 2.2 ± 0.3 mm, respectively; P = .86). There were no significant changes in heart rate or blood pressure after PPI measurements ( P = .46 and .49, respectively). Bispectral index was slightly increased after PPI measurements ( P = .01; mean bispectral index increase <5%). No withdrawal movements occurred during PPI measurements. CONCLUSIONS: There was a significant decrease in PPI after alfentanil administration. The results of this pilot study suggest that PPI score decreases when the level of analgesia increases. PPI measurement was not associated with a clinical or hemodynamic nociceptive response. This new index might provide useful information to individually adapt opioid administration before nociceptive stimuli under general anesthesia.